D-Dimer Is a Predictive Factor of Cancer Therapeutics-Related Cardiac Dysfunction in Patients Treated With Cardiotoxic Chemotherapy - Oikawa, Masayoshi; Yaegashi, Daiki; Yokokawa, Tetsuro; Misaka, Tomofumi; Sato, Takamasa; Kaneshiro, Takashi; Kobayashi, Atsushi; Yoshihisa, Akiomi; Nakazato, Kazuhiko; Ishida, Takafumi; Takeishi, Yasuchika (Frontiers in Cardiovascular Medicine, 2022)
Background D-dimer is a sensitive biomarker for cancer-associated thrombosis, but little is known about its significance on cancer therapeutics-related cardiac dysfunction (CTRCD). Methods Consecutive 169 patients planned for cardiotoxic chemotherapy were enrolled and followed up for 12 months. All patients underwent echocardiography and blood test at baseline and at 3-, 6-, and 12 months. Results The patients were divided into two groups based on the level of D-dimer (>1.65 μg/ml or ≦ 1.65 μg/ml) at baseline before chemotherapy: high D-dimer group (n = 37) and low D-dimer group (n = 132). Left ventricular ejection fraction (LVEF) decreased at 3- and 6 months after chemotherapy in high D-dimer group [baseline, 65.2% (62.8–71.4%); 3 months, 62.9% (59.0–67.7%); 6 months, 63.1% (60.0–67.1%); 12 months, 63.3% (58.8–66.0%), p = 0.03], but no change was observed in low D-dimer group. The occurrence of CTRCD within the 12-month follow-up period was higher in the high D-dimer group than in the low D-dimer group (16.2 vs. 4.5%, p = 0.0146). Multivariable logistic regression analysis revealed that high D-dimer level at baseline was an independent predictor of the development of CTRCD [odds ratio 3.93, 95% CI (1.00–15.82), p = 0.047]. Conclusion We should pay more attention to elevated D-dimer levels not only as a sign of cancer-associated thrombosis but also the future occurrence of CTRCD.